2021
DOI: 10.1177/2325967121993233
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid Bone Loss Is a Risk Factor for Poor Clinical Results After Coracoid Transfer in Rugby Players With Shoulder Dislocations

Abstract: Background: Although surgical shoulder stabilization via coracoid transfer in collision athletes is effective and has a low reinjury rate, the factors affecting poor clinical results and the superiority of the 2 stabilization procedures (Bristow and Latarjet) remain unclear. Purpose: To explore the factor(s) affecting poor clinical results of coracoid transfer in a large cohort of rugby players and to compare postoperative function between the Bristow and Latarjet procedures. Study Design: Cohort study; Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…15,41,42,47 Although previous authors have evaluated the influence of these variables on the clinical outcome following an open Latrerjet procedure, only a few have evaluated their association with patient-reported outcome, with conflicting findings. 3,32 We did not identify an association between radiological injury-related variables and patient-reported outcome. Our findings suggest that while such injury-related factors play a role in the choice of stabilization and risk of clinical failure, they do not significantly influence patient-reported outcome when combined with other patient-related risk factors.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…15,41,42,47 Although previous authors have evaluated the influence of these variables on the clinical outcome following an open Latrerjet procedure, only a few have evaluated their association with patient-reported outcome, with conflicting findings. 3,32 We did not identify an association between radiological injury-related variables and patient-reported outcome. Our findings suggest that while such injury-related factors play a role in the choice of stabilization and risk of clinical failure, they do not significantly influence patient-reported outcome when combined with other patient-related risk factors.…”
Section: Discussionmentioning
confidence: 74%
“…31 In contrast, few studies have evaluated the influence of such a wide range of patient-and injury-related variables on patient-reported outcome following an open Latarjet procedure in the general population (Table VII). 3,31,32 Di Giacomo et al 3 reported on patient-related risk factors influencing clinical failure (defined as a WOSI score of < 70% of normal), identifying female sex and bilateral shoulder instability as risk factors for failure. Other authors have assessed PROMs following an open Latarjet procedure in selected subgroups only, including those with a previously failed arthroscopic Bankart repair, [9][10][11][12] elite athletes, [32][33][34][35][36] those with epilepsy, 13 and those aged ≥ 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawasaki et al 15 reported an association between lower postoperative functional scores and the extent of GBL after Bristow procedures combined with a Bankart repair in competitive rugby players. Their colleagues, Shibuya et al, 31 reported on a similar study that included shoulders treated with either the Bristow or the Latarjet procedure and found an association between the simultaneous presence of a low Rowe score and a high WOSI, which they defined as “functional failure,” and the extent of GBL. On the other hand, Tasaki et al 33 compared postoperative outcomes in 2 groups, one with <10% GBL and the other with >10% GBL, and concluded that GBL does not influence postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%